Clinical characteristics and outcomes of South-East Asian patients with Takotsubo (stress-induced) cardiomyopathy. (December 2018) - Kow, Kristopher; Watson, Timothy James; Foo, David; Ho, Hee Hwa
Abstract: Background: There is limited data on the natural history of Takotsubo (stress-induced) cardiomyopathy in South-East Asian patients. We aim to evaluate the clinical characteristics, predisposing factors and outcomes of patients diagnosed with Takotsubo cardiomyopathy in our region. Methods: From January 2010 to March 2017, 98 patients were diagnosed with Takotsubo cardiomyopathy in our institution. Data were collected retrospectively on baseline clinical characteristics, presenting symptoms, precipitating factors, clinical investigations and in-hospital clinical outcomes. Results: 82% of the patients were female. An antecedent physical stressor was more common than emotional trigger with 35% of patients having no identifiable stressor. The most common presenting symptoms were chest pain (53.1%), dyspnea (45%) and diaphoresis (18.5%). The apical variant (89%) was the most common form of Takotsubo cardiomyopathy followed by the mid-ventricular type (5.1%). The mean left ventricular ejection fraction was 35 ± 11%. In-hospital mortality due to cardiovascular causes was 4.1%. 38% of patients developed in-hospital complications. By multi-variable analysis, lower left ventricular function was an independent predictor of in-hospital complication. Conclusion: South-East Asian patients with Takotsubo cardiomyopathy are characterised by female predominance, higher incidence of physical triggers and low cardiovascular mortality. Lower left ventricular function was an independent predictor of adverse outcomes.